Brain morphology correlates of interindividual differences in conditioned fear acquisition and extinction learning - Winkelmann, Tobias; Ruttorf, Michaela; Schad, Lothar R.; Flor, Herta (Brain structure & function, 2016)
The neural circuits underlying fear learning have been intensively investigated in pavlovian fear conditioning paradigms across species. These studies established a predominant role for the amygdala in fear acquisition, while the ventromedial prefrontal cortex (vmPFC) has been shown to be important in the extinction of conditioned fear. However, studies on morphological correlates of fear learning could not consistently confirm an association with these structures. The objective of the present study was to investigate if interindividual differences in morphology of the amygdala and the vmPFC are related to differences in fear acquisition and extinction learning in humans. We performed structural magnetic resonance imaging in 68 healthy participants who underwent a differential cued fear conditioning paradigm. Volumes of subcortical structures as well as cortical thickness were computed by the semi-automated segmentation software Freesurfer. Stronger acquisition of fear as indexed by skin conductance responses was associated with larger right amygdala volume, while the degree of extinction learning was positively correlated with cortical thickness of the right vmPFC. Both findings could be conceptually replicated in an independent sample of 53 subjects. The data complement our understanding of the role of human brain morphology in the mechanisms of the acquisition and extinction of conditioned fear.
Gesehen am 21.05.2019
Published online: 26 February 2015